Law Enforcement for Crime of Pornography Widespread on Social Media Based on lex specialis derogat legi generalis - Hidayat, Ahmad; Irawan, Anang Dony (Faculty of Law, University of Muhammadiyaha Surabaya, 2022)
The spread of pornography cases that are rampant on social media has resulted in an increase in immoral acts and obscenity. As in the case of the spread of Vina Garut's nasty video between a woman and three men circulating on social media. The crime of pornography is an act related to images, illustrations, photos, writings, sounds, moving images, gestures, or other forms of messages through various forms of communication media and/or public performances. Specifically, social media that contains obscenity or exploitation of sexual behavior violates the norms of decency in society. The formulation of the problem in this paper is first, how is the responsibility for the crime of pornography that spreads it through social media. Secondly, how to enforce the law against criminal acts for perpetrators of spreading pornographic content through social media.